2016
DOI: 10.1176/appi.ps.201500280
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Mental Health Service Use by Young Adults: A Systematic Review

Abstract: Objective: The purpose of this review was to systematically evaluate the available heterogeneous research examining determinants of mental health service use among young adults.Methods: Nine electronic databases were searched to identify quantitative studies examining sociodemographic and psychological variables predictive of or associated with mental health service use. Included studies were examined against the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines. Effect s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 68 publications
3
28
1
Order By: Relevance
“…Prominent facilitator themes in help-seeking In terms of enablers of psychological help-seeking, only a few facilitators were mentioned in the studies, which supported findings in other studies asserting that factors that promote help-seeking are less often emphasized [42,51].…”
Section: Filipino Mental Health Help-seeking Behavior and Attitudessupporting
confidence: 81%
See 2 more Smart Citations
“…Prominent facilitator themes in help-seeking In terms of enablers of psychological help-seeking, only a few facilitators were mentioned in the studies, which supported findings in other studies asserting that factors that promote help-seeking are less often emphasized [42,51].…”
Section: Filipino Mental Health Help-seeking Behavior and Attitudessupporting
confidence: 81%
“…The presence of friends and family can discourage Filipinos from seeking professional help because their social support serves as protective factor that buffer one’s experience of distress [ 77 , 78 ]. Consequently, individuals are less likely to use professional services [ 42 , 79 ]. On the contrary, other studies have found that the presence of friends and family who have positive attitudes towards formal help-seeking can promote the utilization of mental health services [ 8 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other related reviews have been restricted to young adults [ 98 ] or to one country only [ 99 ]. While the results reported here are broadly consistent with the findings of these reviews, this study extends previous research by (a) comparing results across settings; (b) including only population-based studies to ensure the generalisability of findings; (c) examining a set of symptoms that typically present together in community settings, making the results a stronger basis for informing interventions at the population level; and (d) separating service utilisation by adults from that of children or adolescents, since in many countries services are delivered separately for these two groups, and decisions regarding treatment-seeking may follow different paths for minors (defined here as those aged under 18).…”
Section: Discussionmentioning
confidence: 99%
“…However, later studies suggested that traditionally emphasized barriers such as stigma 'clearly are not the entire story' and that it is possible that stigma takes more subtle forms, like self-stigma within university, which asks for a closer look in future research [16,19]. More recent studies demonstrated that not stigma, but intention to seek help was the most influential predictor of the utilization of mental health services [17,36]. Although our results do not support this finding directly, they did point in the same direction: help-seeking was predicted by attitudes to disclose, which are preceded by intentions.…”
Section: Discussionmentioning
confidence: 99%